Mediating role of gut microbiota on Baduanjin for cognitive function in community-dwelling older adults with mild cognitive impairment: a study protocol for a cluster randomised controlled trial - Guohua Zheng; Liwei Sun; Qian Geng (BMJ Open)
Introduction The gut microbiome plays an important role in maintaining both cognitive and physical functions in older adults, and gut dysbiosis is an important pathophysiological mechanism of mild cognitive impairment (MCI) in older adults. As a typical traditional Chinese mind-body exercise, regular Baduanjin training has been shown to improve cognitive function and modulate the gut microbiome in community-dwelling older adults. However, the potential role of the gut microbiome in the benefits of Baduanjin on cognitive function remains unclear. The aim of this study is to investigate the mediating effect of gut microbiome between regular Baduanjin training and improvement in cognitive function in community-dwelling older adults with MCI.Methods and analysis This is a two-arm, randomised, parallel-controlled, single-blinded trial. Four residential communities (clusters) with a total of 64 eligible participants (16 participants in each residential community) will be randomised 1:1 to either the 24-week Baduanjin exercise intervention group (60 min per session, four sessions per week) or the no specific exercise intervention control group. Global cognitive function and the subdimensions of cognition including executive function, visuospatial function, language function and memory function will be assessed using the Montreal Cognitive Assessment Scale, Trail Making Test, Auditory Verbal Learning Test, Boston Naming Test-30 and Clock-Drawing Test, while the gut microbiome and its metabolomics will be detected using 16S rRNA and ultra-high-performance liquid chromatography–tandem mass spectrometry at baseline and at the end of 24-week intervention. The intervention effect of Baduanjin exercise and mediating role of gut microbiota will be analysed using linear mixed models and the bootstrapping method in the Hayes process.Ethics and dissemination This study conforms to Declaration of Helsinki principles and relevant ethical guidelines. Ethical approval has been obtained from the Ethics Committee of the Shanghai University of Medicine and Health Sciences (approval number: 2023-GZR-011). Written informed consent will be obtained from all participants. Results will be disseminated to relevant groups in peer-reviewed journal(s), and at relevant international or national scientific conferences. Key findings will also be shared with social media, healthcare providers, participants or community-dwelling older adults to support access for non-research audiences.Trial registration number ChiCTR2300078147.